Survival Status and Predictors of Mortality among Multidrug-Resistant Tuberculosis Patients in Saint Peter’s Specialized Hospital, Addis Ababa, Ethiopia - Mikyas Arega Muluneh; Abayneh Birlie Zeru; Behailu Tariku Derseh; Abebaw Molla Kebede (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Multidrug-Resistant Tuberculosis (MDR-TB) is tuberculosis that is resistant to at least both rifampicin and isoniazid. The World Health Organization as reported in 2019 revealed that Ethiopia is among the 20 countries with the highest estimated numbers of incident MDR-TB cases. However, supporting evidence is limited in the study area after the Ethiopian national strategic plan for tuberculosis prevention and control is started. Objective. To determine survival status and predictors of mortality among multidrug-resistant tuberculosis patients treated in Saint Peter’s Specialized Hospital at Addis Ababa, Ethiopia, 2020. Methods. An institutional retrospective cohort study was conducted using all MDR-TB patients who were enrolled in Saint. Peter’s Specialized Hospital from January 01, 2015, to December 31, 2017. A pretested data extraction form that had 5 items for sociodemographic and 15 items for the measurement of clinical characteristics of 484 MDR-TB patients was used. STATA software version 14.2 was used for data cleaning and analysis. A variable that fitted in the bivariable Cox proportional hazard model at p value <0.25 was used in the final multivariable Cox proportional hazard model, and independent predictors of time to event were determined at a p value of 0.05. Result. A total of 484 patients were followed up for 5,078 person-months. Among the total patients, nearly half, 238 (48.8%), were males. The median age of patients was 30 years (interquartile range (IQR), 24–39), and 56 (11.6%) were aged between 1 and 19 years. During the follow-up period, 315 (65.1%) patients were cured, 125 (25.8%) completed treatment, 24 (5%) died, and 20 (4.1%) were lost to follow-up. The overall cumulative probability survival of the patients at the end of treatment was 94.85% (95% confidence interval (CI): 92.38%–96.53%). The independent predictors of time to death were being anemic (AHR = 3.65; 95% CI: 1.36, 9.79), having clinical complication (AHR = 3; 95% CI: 1.2, 7.5), and being HIV infected (AHR = 5.8; 95% CI: 2.2, 15.7). Conclusions. MDR-TB patients’ survival rate was high in St Peter’s Specialized Hospital. MDR-TB patients with anemia, HIV coinfection, and clinical complications had higher risk of mortality. So, prevention and controlling of anemia, HIV/AIDS, and clinical complications will reduce the mortality of MDR-TB patients.